2022
DOI: 10.4103/ijn.ijn_468_20
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open surgery catheter placement in peritoneal dialysis patients: A meta-analysis of outcomes

Abstract: Introduction: The peritoneal dialysis catheter (PDC) can be placed either through the laparoscopic technique, percutaneous technique, or surgical procedures. The utilization of these PDC placement procedures is based on the successful placement and reduced risk of development of complications. The main objective of this study was to compare the complications associated with the laparoscopic technique to those linked to open surgery during PDC placement. Methods: The lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The one-year catheter survival rate was higher in the laparoscopic group compared to the open surgery group, but in the other study, this difference was not found [51,55]. Dialysate leakage, exit-site infection, and peritonitis incidence between the laparoscopic and open surgery groups were similar [56].…”
Section: Outcomes Of Different Pd Catheter Placement Approachesmentioning
confidence: 71%
“…The one-year catheter survival rate was higher in the laparoscopic group compared to the open surgery group, but in the other study, this difference was not found [51,55]. Dialysate leakage, exit-site infection, and peritonitis incidence between the laparoscopic and open surgery groups were similar [56].…”
Section: Outcomes Of Different Pd Catheter Placement Approachesmentioning
confidence: 71%
“…Recent advancements have introduced alternatives to traditional glucose-based dialysates, such as buffered solutions 2 , 3 and isodextrin-based options 4 , aiming to improve biocompatibility and reduce the risk of complications, such as peritoneal sclerosis 5 , 6 . Effective PD relies heavily on successful catheter placement, with techniques ranging from conventional surgical to minimally invasive percutaneous methods 7 10 . These advancements have made PD more accessible and adaptable to various clinical settings.…”
Section: Introductionmentioning
confidence: 99%